Characteristics and prognosis of patients with primary metastatic disease vs. recurrent HER2-negative, hormone receptor-positive advanced breast cancer - Walter, Christina; Hartkopf, Andreas; Hein, Alexander; Fasching, Peter Andreas; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Lüftner, Diana; Wallwiener, Markus; Müller, Volkmar; et al. (The breast, 2025)
Background - Patients with first-line metastatic breast cancer (MBC) comprise patients with de novo metastases (dnMBC) or recurrent disease after primary breast cancer (rMBC). This analysis aimed to explore the prognostic value of dnMBC versus rMBC overall and particularly in subgroups according to age and metastasis site, in addition to other prognostic clinicopathological parameters in a first-line, hormone receptor (HR)-positive, HER2-negative (HRpos/HER2neg) population. - Methods - Within the prospective PRAEGNANT MBC registry (NCT02338167), 508 HRpos/HER2neg patients, receiving first-line treatment for advanced disease, were identified. Clinicopathological parameters (age, body mass index, performance status, tumor grading, metastasis site and therapy) were assessed according to metastatic status (dnMBC, rMBC within 5 years of primary diagnosis (rMBC <5 years), rMBC after more than 5 years (rMBC ≥5 years)). Cox regression analyses were performed to investigate whether metastatic status influences progression-free survival (PFS) and overall survival (OS). - Results - De novo metastatic disease was present in 180 patients (35.4 %), whereas 132 patients (26.0 %) had rMBC <5 years and 196 patients (38.6 %) had rMBC ≥5 years. Patients with dnMBC had the most favorable prognosis. Relative to dnMBC, hazard ratios for PFS were 1.75 (95%CI: 1.31-2.34) in rMBC<5 years and 1.25 (95%CI: 0.94-1.65) for rMBC ≥5 years. Subgroup-specific differences were not observed. - Conclusion - HRpos/HER2neg first-line MBC patients have a more favorable prognosis if the disease was previously not treated. This difference was similar across all examined clinicopathological parameters. It may therefore be beneficial to incorporate MBC categories as a stratification factor in clinical trials.
Online veröffentlicht am 5. Februar 2025, Artikelversion: 13. Februar 2025
Gesehen am 22.12.2025